Pengaruh Manajemen Kelas terhadap Motivasi Belajar Siswa Kelas IV SD Negeri 0513 Aek Lancat - Mancar; Dumaria Pulungan; Era Mutiah (Dirosah Islamiyah, 2026)
This study aimed to determine the effect of classroom management on the learning motivation of fourth-grade students at SD Negeri 0513 Aek Lancat, Lubuk Barumun District, Padang Lawas Regency. The research employed a quantitative approach using questionnaires to collect data on classroom management and students’ learning motivation. The results showed that the average score of the classroom management questionnaire was 54.70, while the average score of the learning motivation questionnaire was 55.47. Data analysis was conducted using simple linear regression with the assistance of IBM SPSS Statistics software. The analysis was carried out to examine the relationship and influence between classroom management and students’ learning motivation. Based on the regression analysis, the significance value obtained was below the predetermined level of significance, indicating a significant linear relationship between the two variables. Furthermore, hypothesis testing was conducted using the Independent Sample T-Test with the support of IBM SPSS Statistics software. The results revealed a Sig. (2-tailed) value of 0.003, which was lower than 0.05. According to the established criteria, if the Sig. (2-tailed) value is less than 0.05, the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that classroom management has a significant positive influence on the learning motivation of fourth-grade students at SD Negeri 0513 Aek Lancat.